Evolution of three Pyrenophora cereal pathogens: recent divergence, speciation and evolution of non-coding DNA - Ellwood, Simon; Syme, Robert; Moffat, C.; Oliver, Richard (Elsevier Inc., 2012)
Three of the most important fungal pathogens of cereals are Pyrenophora tritici-repentis, the cause of tan spot on wheat, and Pyrenophora teres f. teres and Pyrenophora teres f. maculata, the cause of spot form and net form of net blotch on barley, respectively. Orthologous intergenic regions were used to examine the genetic relationships and divergence times between these pathogens. Mean divergence times were calculated at 519 kya (±30) between P. teres f. teres and P. teres f. maculata, while P. tritici-repentis diverged from both Pyrenophora teres forms 8.04 Mya (±138 ky). Individual intergenic regions showed a consistent pattern of co-divergence of the P. teres forms from P. tritici-repentis, with the pattern supported by phylogenetic analysis of conserved genes. Differences in calculated divergence times between individual intergenic regions suggested that they are not entirely under neutral selection, a phenomenon shared with higher Eukaryotes. P. tritici-repentis regions varied in divergence time approximately 5–12 Mya from the P. teres lineage, compared to the separation of wheat and barley some 12 Mya, while the P. teres f. teres and P. teres f. maculata intergenic region divergences correspond to the middle Pleistocene. The data suggest there is no correlation between the divergence of these pathogens the domestication of wheat and barley, and show P. teres f. teres and P. teres f. maculata are closely related but autonomous. The results are discussed in the context of speciation and the evolution of intergenic regions.